The dynamic recrystallization induced by Al2Nd and promoted by Al2RE in a hot compressed Mg–1Al-1.5Nd-1.5Y-0.5Gd alloy - Shengquan Liang; Qianlong Ren; Xiaowei Li; Shiyu Luan; Xiaoqiang Li; Peipeng Jin; Jinhui Wang (Journal of Materials Research and Technology)
The workability of rare earth magnesium alloys is deteriorated due to work hardening after extrusion deformation, significantly impacting their application in the automotive and aerospace industries. In this study, the effects of various hot working parameters on the microstructure and hardness of an extruded Mg–1Al-1.5Nd-1.5Y-0.5Gd alloy were investigated including strain rate ranging from 0.001 s⁻1 to 1 s⁻1 and deformation temperature between 300 °C and 450 °C. The results indicate that the average grain size of the hot compressed alloy was significantly refined to only 3.59 μm under the strain rate of 0.01 s⁻1 and the deformation temperature of 400 °C, representing a 36% reduction of average grain size compared to as-extruded alloy. Additionally, the Vickers hardness of hot compressed alloy was improved to 58.5 HV, indicating a 31% increase of hardness relative to the specimens at extruded condition. During thermal deformation, recrystallization was induced by the Al₂Nd phase, while nucleation was stimulated by the Al₂RE (Y, Nd, Gd) phase to promote recrystallization. Below 350 °C, the nucleation effect of Al₂RE particles served as the primary driving force for dynamic recrystallization (DRX). However, as temperature increases, the refinement of grains was progressively dominated by the Al₂Nd phase through the induction of dislocation walls. The different impacts of various second phases on DRX behavior were underscored. At 400 °C, the critical temperature for the formation of dislocation walls and the transformation of substructures, a fine-grained microstructure with a high dislocation density was exhibited by the hot-worked alloy, resulting in enhanced hardness.